The descriptive database: A design of Conceptual object oriented model - Herrera Delgado, Lizbeth Berenice (2017)
The present theoretical article is the result of an investigation that combines the Systems Engineering and the Library Sciences; it shows an interdisciplinary approach to the problem presented by the descriptive databases of the digital library, problematic generated by the change in the principles of organization of the information and the demands that the digital environment imposes to the libraries. The analysis leads to a rethinking about the construction of descriptive databases, migrating from the Entity–relationship Model (ER model) to adopt the Object-oriented Modeling (OOM), which is currently used for the construction and programmatic development of the semantic web. Therefore, this theoretical article proposes an Object-oriented Conceptual Modeling under its own methodology, which it develops the process to generate the proposed model in two stages. The first is to approach the problem, while the second corresponds to the identification of elements that includes elements of the Resources, Description and Access (RDA) rules and observes the theoretical principles that establish the Functional Fequirements for Bibliographic Records (FRBR). Already as a whole, all data are analyzed to generate the design proposal of three object-oriented conceptual modeling for descriptive databases: 1) the Work model, 2) the Domain model, and 3) the Instance model, to form a more adequate and descriptive database of the library in this digital era.